ER Stress is Activated and Involved in Disuse-Induced Muscle Atrophy - Lu Wang; Xiangsheng Pang; Shiming Li; Wenjiong Li; Xiaoping Chen; Peng Zhang (Frontiers in Bioscience-Landmark, 2023)
Background: Muscle atrophy resulting wholly or partially from disuse represents a serious medical complication that decreases quality of life and increases morbidity and mortality. The accumulation of misfolded/unfolded proteins disrupts endoplasmic reticulum (ER) homeostasis and thus causes ER stress. Growing evidence indicates that ER stress plays an essential role in skeletal muscle remodeling under various physiological or pathophysiological conditions. However, whether ER stress is involved in disuse-induced muscle atrophy remains unclear. Methods: To induce muscle atrophy, 8-week-old C57BL/6JNifdc male mice were subjected to 3, 7, or 14 days of hindlimb unloading (HU), and rhesus macaques (Macaca mulatta) were subjected to 10∘ head-down tilted bed rest (HDBR) for 6 weeks. Tauroursodeoxycholic acid (TUDCA) (500 mg/kg/d) was orally administered to mice during HU to inhibit ER stress. Quantitative PCR, Western blotting, and immunohistochemistry were conducted to evaluate gene, protein, and structural changes, respectively. Results: ER stress marker genes were rapidly induced by HU in a similar trend to that observed with atrophy-related genes such as Atrogin-1, muscle RING finger 1 (MuRF1), and muscle ubiquitin ligase of SCF complex in atrophy-1 (MUSA1). Inhibition of ER stress with TUDCA, a pan-ER stress inhibitor, attenuated HU-induced muscle atrophy and the upregulation of ubiquitin ligases via the AKT/forkhead box O3a pathway. In addition, the oxidative-to-glycolytic myofiber type transition caused by HU was also inhibited by TUDCA treatment. ER stress activation was also confirmed in HDBR-induced rhesus soleus muscle atrophy. Conclusions: The strong positive correlation between ER stress activation and both HU- and HDBR-induced muscle atrophy indicates that ER stress activation is ubiquitously involved in disuse-induced muscle atrophy, regardless of species. Thus, inhibiting ER stress may be an effective therapeutic strategy to prevent muscle atrophy during disuse.